Unusual clustering of brain tumours in a family with NF1 and variable expression of cutaneous features. Issue 12 (1st December 1999) - Faravelli, F; Upadhyaya, M; Osborn, M; Huson, S M; Hayward, R; Winter, R
Abstract : Neurofibromatosis type 1 (NF1) is one of the commonest autosomal dominant disorders in man. It is characterised by café au lait spots, peripheral neurofibromas, Lisch nodules, axillary freckling, skeletal dysplasia, and optic glioma. Symptomatic brain tumours occur in 1.5-2.2% of patients with NF1. We report here a family where seven members developed brain tumours. Of these, three have a clinical history strongly suggestive of NF1, while two do not fulfil diagnostic criteria for the disorder. A splice site mutation in exon 29 of the NF1 gene was found in these two subjects. This lesion is thought to be disease causative since it creates a frameshift and a premature termination of the neurofibromin protein. Different hypotheses to explain the unusual recurrence of brain tumours in this family, such as the nature of the mutation or cosegregation of other predisposing genes, are discussed.